Approach of education in African traditions by the prism of Emile Jean-Jacques Rousseau - (:unkn) unknown (My University, 2014)
Education is one of the questions that arises humanity. From the ideal of Rousseau, including the African traditional approach, appear in the philosophic and anthropological conceptions an interrogation inherent to the man and his condition. It is about an approach which allows seizing the spirit of the education in the general context of the human existence. This quest of the human essence through the child allowed us to understand, how the individual can be shaped by his environment and by the adults. So, it seems that all the humanity educates at first according to its vision of man and values of his own; even if it has to aim at the universal. As a matter of fact, the human future is the resultant of models which are transmitted by the education.
Keywords: African Research